The combination of ITS2 and psbA-trnH region is powerful DNA barcode markers for authentication of medicinal Terminalia plants from Thailand - Aekkhaluck Intharuksa (2020)
© 2019, The Japanese Society of Pharmacognosy. The dried fruits of Terminalia plant (Combretaceae) called “Samo” have been used as herbal medicine in Thai traditional medicine. Four “Samo” crude drugs, namely, Samo thai, Samo thed, Samo dee-ngu, and Samo phiphek, are used as the main ingredients in Triphala and Trisamo recipes. Their commercial products are available in processed and powdered form, but are difficult to authenticate by conventional methods. In this study, we aimed to discriminate species of genus Terminalia for the identification of their crude drugs by a DNA barcoding technique. A total of 208 closely related nucleotide sequences were obtained from nine Terminalia species collected from Thailand and the DDBJ/EMBL/GenBank database. An effective DNA barcode marker was selected from six DNA loci (matK, rbcL, psbA-trnH, ITS, ITS1, and ITS2) and their two-locus combination. All sequences were analyzed by three major methods: (1) BLAST search; (2) the genetic divergence method using Kimura 2-parameter (K2P) distance matrices; and (3) tree topology analysis based on the neighbor-joining method. Comparison of the six candidate DNA loci indicated that ITS identified Terminalia with 100% accuracy at the species and genus levels in the BLAST1 method. ITS2 showed the highest K2P variability. The data from the single markers and the two-locus combinations revealed that only the two-locus combinations, namely, the combinations of rbcL, ITS, ITS1, and ITS2 with psbA-trnH, clearly discriminated all the species. From the results of DNA sequence analysis and the three methods, ITS2 is recommended for the identification of Terminalia species to supplement psbA-trnH.